Analisis Ketepatan Pendistribusian Rekam Medis Rawat Jalan Terhadap Efektivitas Pelayanan Di RSUD Kota Bandung - Ade Irma Suryani; Firjatullah, Tia Qurota Aeni (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
The distribution of medical record document is very important for the ongoing effective health service activities, the faster the medical record document reach the service unit, the faster the patient will get the health services provided by the doctor. The distribution of medical records is required to meet minimum service standards of ? 10 minutes from the provision of medical record document, the purpose of this study was to analyze the distribution of medical record document at Bandung City Hospital, this type of research uses a qualitative approach, data collection through interviews and observation with a sample size 100 medical records document and 20 distribution officers and polyclinic nurses at Bandung City Hospital were taken. The percentage of timeliness according to the minimum service standard is 79 document (79%) with an average distribution time of 3,6 minutes and those that do not meet the standard are 21 document (21%) with an average distribution time of 12 minutes. It is also known that there are 88 record document medical record document (88%) were correct at the polyclinic, while medical record document were incorrect at the intended polyclinic as many as 12 medical record document (12%), and according to the survey results determined the effectiveness of the distribution of medical record document at Bandung City Hospital, namely 72%. The conclusion of this study is that there are still delays in the distribution time and inaccuracy of medical record document to the intended polyclinic at Bandung City Hospital, by increasing the evaluation of medical record officers, especially distribution, also adding distribution officers can increase the number of medical record document that meet minimum service standard ? 10 minutes.